Evaluation of dynamic changes and formation regularity in volatile flavor compounds in Citrus reticulata 'chachi' peel at different collection periods using gas chromatography-ion mobility spectrometry. (15th December 2022) - Liu, Haocheng; Wen, Jing; Xu, Yujuan; Wu, Jijun; Yu, Yuanshan; Yang, Jiguo; Liu, Haiyang; Fu, Manqin
Abstract: Citrus reticulata 'Chachi' is a commercially important and predominantly cultivated tangerine cultivar in Xinhui County, Guangdong, China. The dried C. reticulata 'Chachi' pericarp (CRCP), known as "Guangchenpi" in Mandarin has unique flavor properties, and has been used as a highly valuable nutritional food source and in traditional medicine for centuries. In this study, headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS) and partial least squares-discriminant analysis (PLS-DA) were adopted to rapidly and comprehensively evaluate the flavor compounds of dried CRCP, and to identify their dynamic changes at different fruit picking stages. Results revealed a total of 71 volatile compound in the samples at six different fruit picking stages. The C6 –C9 alcohols and aldehydes with aromatic green grass profiles had higher concentrations in the early fruit picking stages (from July to October), while most terpenes, ketones, and esters with typical aromas of mature flowers and fruits were highly accumulated in the late fruit picking stages (from November to December). PLS-DA results showed that samples picked in different stages could effectively be divided into relatively independent clusters, and the variable importance in projection (VIP) models identified 12 representative flavor compounds, which could be used as flavor markers for distinguishing CRCP samples picked at different stages. Graphical abstract: Image 1 Highlights: GC-IMS combined with PLS-DA is a rapid, reliable method to assess the aroma in CRCP. The key differential VOCs in CRCP were screened out by flavor fingerprint. The "fruity" note increased in the CRCP at a late stage of picking (Nov.–Dec.). The samples during the Jul.–Oct. Period are based on the "green" of C6 and C9 VOCS . PLS-DA confirmed 12 key characteristic flavor substances in all picking stages.